Behavior Change Interventions Combating Online Misinformation: A Scoping Review - Konstantinou, Loukas; Karapanos, Evangelos (My University, 2025)
It is increasingly acknowledged that simply presenting users with corrective information is unlikely to produce the desired effects against misinformation. As such, the need for systematic use of behavioral theory is increasingly acknowledged, and behavioral interventions against misinformation are rising. This paper presents a scoping review of digital behavioral interventions countering misinformation, inquiring into their behavioral objectives, theoretical foundations, design and evaluation practices, and the factors that were empirically proven, or speculated, to contribute to interventions' failure. Among others, we identify 17 distinct behavioral objectives, organized into three stages of the online news cycle: composition, amplification and consumption, 24 theoretical frameworks employed in designing these interventions, and nine reasons of failure. We synthesize the findings into a set of design cards with the goal of guiding intervention designers during concept ideation and refinement, and highlight areas for future research.
Keywords: Attitude Change; Behavior Change; Online Misinformation; Scoping Review